PELATIHAN DESIGN BUILDING INFORMATION MODELLING (BIM) DENGAN SKETCHUP DI SMK NEGERI 6 KOTA BEKASI - Hadian Mukhlisha Irfani; Setyo Supratno (An-Nizam, 2022)
Field Work Lecture (KKN) is one of the activities carried out by all students of the 45 Bekasi Islamic University to apply the knowledge gained while sitting in lectures as well as a real form of community service. To help support KKN (Field Work Lectures) activities, a training program related to the 2021/2022 period KKN (Field work lectures) activity program is needed. The purpose of this training program is to improve the knowledge, attitudes and skills of students in SMK about building drawing technology using 3D (three-dimensional) SketchUp. This program discusses the stages in drawing a one-story residential building technique using the 3D (three-dimensional) digital method. There are many kinds of computer applications that are used to draw in 3D (three dimensions). Although there are many, the SketchUp application was chosen as an interesting solution for drawing 3D (three- dimensional) buildings, because using this application the process is not too difficult. From the results of the training carried out, it can be said that building design can be more effective and efficient if it is implemented into a three-dimensional design, so that the final results can be presented.